Carinal resection and reconstruction following inflammatory myofibroblastic tumor resection: A case report - Julia G. Lyon; Lauren A. Kilpatrick; Tara L. Rosenberg; Abby R. Nolder; Michiaki Imamura; Gresham T. Richter (Elsevier, 2016)
Inflammatory myofibroblastic tumors (IMT) are rare tumors of the respiratory tract that most commonly occur in the lung and are rarely seen in the trachea. They present most often in young patients. We report on a case of an IMT of the carina in a seven year old girl, requiring carinal resection and reconstruction with a novel technique in pediatric airway surgery. Attempts at endoscopic excision of the carinal IMT were unsuccessful. An open approach for resection of the involved carina, distal trachea, and proximal mainstem bronchi was performed via sternotomy and cardiopulmonary bypass. The resulting triangular defect in the trachea and bronchi was reconstructed with anastomosis of the proximal trachea and left mainstem bronchus using a rotational flap of the right lateral mainstem bronchial wall. The remaining right mainstem bronchus was anastomosed, end to side, to the intact trachea proximal to the primary anastomosis. Bronchoscopy and MRI 22 months post resection and reconstruction revealed a healthy neo-carina and patent distal airway with no evidence of recurrent IMT. Pediatric patients with carinal inflammatory myofibroblastic tumors can be successfully managed with open resection and reconstruction of the airway.